University Social Responsibility Reporting in Alignment with Sustainability Development Goals: A Conceptual Framework - Saraswati, Erwin; Ghofar, Abdul; Atmini, Sari; Dahlan, Muhammad (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 2 (2023), 2023)
Universities must consider the greenhouse gas effect, the biggest component of global warming due to a large amount of electrical energy utilization. Not to mention the use of paper and water, which are irreplaceable resources in relatively significant quantities. Therefore, universities must carry out social responsibility as a form of concern for sustainability. This study aims to design a conceptual framework for the University Sustainability Report (USRR), which aligns with the SDGs. The first thing to do is determine materiality based on the 2016 and 2021 GRI Standard concepts for specific disclosures. The results of the study found that the topics were specific to the economical category - indirect economic impacts (SDGs 1 and 11); environmental category – electricity consumption (SDGs 7 and 12); while the social categories – employee rights (SDGs 16), contributions and donations (SDGs 1), customer satisfaction and service (SDGs 17), welfare and work safety (SDGs 3); training and development (SDGs 4 and 16); and equal opportunities (SDGs 5 and 10). General disclosure refers to SEOJK 16/2021, namely the sustainability strategy; university profile; explanation of the highest leadership, and university governance. The USRR framework is based on materiality findings involving stakeholders.